Interleukin-1 acts via the JNK-2 signaling pathway to induce aggrecan degradation by human chondrocytes - Ismail, H; Yamamoto, K; Vincent, T; Nagase, H; Troeberg, L; Saklatvala, J (Wiley, 2015)
Objective: Aggrecan enables articular cartilage to bear load and resist compression. Aggrecan loss occurs early in osteoarthritis and rheumatoid arthritis and can be induced by inflammatory cytokines such as interleukin‐1 (IL‐1). IL‐1 induces cleavage of specific aggrecans characteristic of the ADAMTS proteinases. The aim of this study was to identify the intracellular signaling pathways by which IL‐1 causes aggrecan degradation by human chondrocytes and to investigate how aggrecanase activity is controlled by chondrocytes. Methods: We developed a cell‐based assay combining small interfering RNA (siRNA)–induced knockdown with aggrecan degradation assays. Human articular chondrocytes were overlaid with bovine aggrecan after transfection with siRNAs against molecules of the IL‐1 signaling pathway. After IL‐1 stimulation, released aggrecan fragments were detected with AGEG and ARGS neoepitope antibodies. Aggrecanase activity and tissue inhibitor of metalloproteinases 3 levels were measured by enzyme‐linked immunosorbent assay. Low‐density lipoprotein receptor–related protein 1 (LRP‐1) shedding was analyzed by Western blotting. Results: ADAMTS‐5 is a major aggrecanase in human chondrocytes, regulating aggrecan degradation in response to IL‐1. The tumor necrosis factor receptor–associated 6 (TRAF‐6)/transforming growth factor β–activated kinase 1 (TAK‐1)/MKK‐4 signaling axis is essential for IL‐1–induced aggrecan degradation, while NF‐κB is not. Of the 3 MAPKs (ERK, p38, and JNK), only JNK‐2 showed a significant role in aggrecan degradation. Chondrocytes constitutively secreted aggrecanase, which was continuously endocytosed by LRP‐1, keeping the extracellular level of aggrecanase low. IL‐1 induced aggrecanase activity in the medium in a JNK‐2–dependent manner, possibly by reducing aggrecanase endocytosis, because IL‐1 caused JNK‐2–dependent shedding of LRP‐1. Conclusion: The signaling axis TRAF‐6/TAK‐1/MKK‐4/JNK‐2 mediates IL‐1–induced aggrecanolysis. The level of aggrecanase is controlled by its endocytosis, which may be reduced upon IL‐1 stimulation because of LRP‐1 shedding.